SISTEM INFORMASI PENJUALAN PADA SUSI SAYUR BERBASIS WEB - Ari, Nopri Apriandi (TEKNOFILE : Jurnal Sistem Informasi, 2024)
Susi Sayur is a place or container that sells various types of vegetables that the local community needs to meet or complete kitchen needs for cooking. The location of Susi Sayur is at Pasar Pagi Jl. Baharuddin Yusuf, Tembilahan, Indragiri Hilir, Riau. In the current digital era, sales online vegetables has become an increasingly popular trend. This concept utilizes technology to facilitate vegetable sales transactions from farmers directly to consumers, eliminating intermediaries and reducing costs. Online vegetable sales not only provide easy access for consumers to get fresh vegetables at more affordable prices, but also help farmers earn better income. However, challenges such as vegetable quality, logistics and consumer confidence still need to be overcome.